Shutdown of HIV-1 Transcription in T Cells by Nullbasic, a Mutant Tat Protein - Hongping Jin (American Society for Microbiology, 2016)
ABSTRACT Nullbasic is a derivative of the HIV-1 transactivator of transcription (Tat) protein that strongly inhibits HIV-1 replication in lymphocytes. Here we show that lentiviral vectors that constitutively express a Nullbasic-ZsGreen1 (NB-ZSG1) fusion protein by the eEF1α promoter led to robust long-term inhibition of HIV-1 replication in Jurkat cells. Although Jurkat-NB-ZSG1 cells were infected by HIV-1, no virus production could be detected and addition of phorbol ester 12-myristate 13-acetate (PMA) and JQ1 had no effect, while suberanilohydroxamic acid (SAHA) modestly stimulated virus production but at levels 300-fold lower than those seen in HIV-1-infected Jurkat-ZSG1 cells. Virus replication was not recovered by coculture of HIV-1-infected Jurkat-NB-ZSG1 cells with uninfected Jurkat cells. Latently infected Jurkat latent 6.3 and ACH2 cells treated with latency-reversing agents produced measurable viral capsid (CA), but little or none was made when they expressed NB-ZSG1. When Jurkat cells chronically infected with HIV-1 were transduced with lentiviral virus-like particles conveying NB-ZSG1, a >3-log reduction in CA production was observed. Addition of PMA increased virus CA production but at levels 500-fold lower than those seen in nontransduced Jurkat cells. Transcriptome sequencing analysis confirmed that HIV-1 mRNA was strongly inhibited by NB-ZSG1 but indicated that full-length viral mRNA was made. Analysis of HIV-1-infected Jurkat cells expressing NB-ZSG1 by chromatin immunoprecipitation assays indicated that recruitment of RNA polymerase II (RNAPII) and histone 3 lysine 9 acetylation were inhibited. The reduction of HIV-1 promoter-associated RNAPII and epigenetic changes in viral nucleosomes indicate that Nullbasic can inhibit HIV-1 replication by enforcing viral silencing in cells. IMPORTANCE HIV-1 infection is effectively controlled by antiviral therapy that inhibits virus replication and reduces measurable viral loads in patients below detectable levels. However, therapy interruption leads to viral rebound due to latently infected cells that serve as a source of continued viral infection. Interest in strategies leading to a functional cure of HIV infection by permanent viral suppression, which may be achievable, is growing. Here we show that a mutant form of the HIV-1 Tat protein, referred to as Nullbasic, can inhibit HIV-1 transcription in infected Jurkat T cell to undetectable levels. Analysis shows that Nullbasic alters the epigenetic state of the HIV-1 long terminal repeat promoter, inhibiting its association with RNA polymerase II. This study indicates that key cellular proteins and pathways targeted here can silence HIV-1 transcription. Further elucidation could lead to functional-cure strategies by suppression of HIV transcription, which may be achievable by a pharmacological method.